Strategi Viralisasi Konten Dakwah di Kanal Youtube - Mazaya, Vyki (Jurnal Komunikasi Islam, 2021)
Currently some da'wah activists are creating da'wah content channels on Youtube and other social media. This study aims to explore the strategy of viralization of the preaching content of Ustadz Abdul Somad, Gus Miftah and Gus Nur on the Youtube channel. Using a descriptive qualitative approach and through observation and documentation techniques, the results of this study reveal that the da'wah video content created by those three Islamic preachers that are considered viral have characteristics, first, the da'wah messages contain a conflict dimension that are likely to attract the curiosity of the audience. Second, technically the da'wah video content has an interesting title, offers a novelty theme, containing humor, answers religious issues clearly, and has quality da'wah material. Third, the da'i must be credible and have a da'wah strategy that is in accordance with the mad'u's needs.